Comparative Performance Of Six Aromatic Rice (Oryza Sativa) Varieties Under Conventional And Sri Method Of Cultivation (Applied Biological Research, 2015)
A field experiment was carried out at BCKVV, West Bengal (India) during  kharif 2011 and 2012 to assess the performance of 6 rice varieties under  conventional and SRI methods of cultivation with respect to growth, yield  and quality parameters. The results revealed that the method of crop  production significantly affected plant height and root length, whereas  varieties exerted significant impact on dry matter accumulation, LAI, root  length and root dry weight. The SRI method produced 58.6 and 21.8%  higher grain and straw yields, respectively, than conventional system. The  rice quality was unaffected by change in cultivation method. Rice variety  ‘Dehrdun’ gave better response with respect to kernel length and L:B ratio  than other varieties under SRI method.. The physico-chemical properties  of soil after harvest was appreciable improved. Among the different  varieties ‘Badsha bhog’ gave higher gross return, net return and B: C ratio  under SRI method.
Keywords: Aromatic rice; SRI; organic cultivation; quality; yield